Obóz dla dipisów – literackie zapisy doświadczenia życia „pomiędzy”. Zaproszenie do tematu - Krupa, Bartłomiej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
This article is a preliminary attempt to read the condition of survivors – those who were imprisoned in the displaced persons camps in occupied Germany just after the war. In this context author considers Tadeusz Nowakowski’s novel Obóz Wszystkich Świętych (Camp of All Saints), full of satire, grotesque and thoroughly soaked with sarcasm. The addition to Nowakowski’s vision is Tadeusz Borowski’s short story Bitwa pod Grunwaldem (Battle of Grunwald), as well as his poems from this time, e.g. Demokratyczne dary (Democratic Gifts), and also Jerzy Zagórski’s reports W południowych Niemczech (In Southern Germany), where the camps for DPs are compared to Henry Moore’s anthropomorphic figures sleeping in the tunnel. Separate reflections are devoted to the fate of Ida Fink, Shoah survivor, who was imprisoned in the Ettlingen camp. The writer mentions this time in the novel Podróż (Travel) and the interviews. Textual analyzes lead the author of the article to the conclusion that the narratives are proof of the inability to experience peace of mind in the time of freedom and generally the inability to return to pre-war times.